Associated Mortality of Liberal Fluid Administration in Sepsis. (October 2019) - Johnson, Mathew R.; Reed, T. Patrick; Lowe, Denise K.; Cahoon, William D.
Fluid resuscitation, to restore intravascular volume and improve oxygen delivery, is a crucial step in early resuscitation efforts of patients with sepsis or septic shock. The 2016 Surviving Sepsis Campaign guidelines suggest the use of dynamic versus static measures of fluid responsiveness and fluid resuscitation with at least 30 mL/kg of intravenous crystalloid within the first 3 hours followed by fluid administration if hemodynamic factors continue to improve. Despite these recommendations, risks to this practice may exist as multiple studies have demonstrated an association between a positive fluid balance and/or administration of large fluid volume and increase in mortality. These studies are limited by variations in their methodologic design; therefore, cause and effect cannot yet be determined. Future multicenter, randomized, controlled studies that evaluate fluid balance and fluid volume need to be conducted to clarify the role of fluid administration to patients with sepsis to maximize benefits and minimize risk.